Design of a Fire Monitoring System Using Web Fire Google Maps and Telegram - Muhammad Nanda Abriel Lanang Pamungkah; M.Teguh Prihandoyo; Eko Budihartono; Muhamad Bakhar (Pt. Anagata Sembagi Education, 2025)
Fire is a type of disaster caused by flames that pose significant threats to human life, infrastructure, vehicles, and the surrounding environment. In Tegal City, there were 40 reported fire incidents in 2017, which drastically increased to 120 incidents in 2018. This alarming rise highlights the urgent need for an effective and responsive fire monitoring system. This research aims to design a real-time fire monitoring system integrated with specifically developed hardware. The methodology involves observation, interviews, and literature studies to ensure the system's relevance and accuracy. The system developed in this study is capable of monitoring multiple registered locations simultaneously through a centralized website. It features real-time data updates, with information being received every second without the need for manual refreshing. Additionally, the system is equipped with a notification and alarm mechanism to provide early warnings when monitored areas are in a state of alert or danger. This innovation is expected to enhance fire disaster preparedness, enable rapid response, and minimize potential damage in vulnerable areas